Method for synthesizing cyclic carbonate by catalyzing conversion of carbon dioxide with ZIF-8-coated In2O3 composite material
The ZIF-8@In2O3 composite catalyst was used to catalyze the cycloaddition reaction of carbon dioxide and epoxides under normal pressure, solving the problems of separation and poor stability of existing catalysts. This enabled the efficient synthesis and easy separation of cyclic carbonates, and has broad application prospects.
Patent Information
- Application Number
- CN202411414023.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
AI Technical Summary
Existing catalysts face challenges in the catalytic conversion of carbon dioxide into cyclic carbonates, including separation difficulties, poor structural stability, low catalytic activity, and the need for high temperature and high pressure, which limits their large-scale application.
ZIF-8@In2O3 composite material was used as a catalyst, which was prepared by in-situ composite of ZIF-8 and hollow prism-structured In2O3, and combined with tetrabutylammonium bromide as a co-catalyst to catalyze the cycloaddition reaction of carbon dioxide with epoxides under normal pressure and mild conditions.
It achieves simple catalyst preparation, cheap and readily available raw materials, high selectivity and stability, and can efficiently synthesize cyclic carbonates under mild conditions. The catalyst and product are easily separated, and it has broad potential for large-scale development.
Smart Images

Figure CN119285598A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of catalytic chemistry, and specifically relates to a ZIF-8@In 2 O 3 A method for synthesizing cyclic carbonates by converting carbon dioxide into catalyzed carbon dioxide using a composite material. Background Art
[0002] The use of fossil fuels in industrial processes has greatly contributed to greenhouse gas emissions, especially carbon dioxide (CO 2 ), which is widely considered to be the main cause of global climate change and ecological degradation. 2 It is also a cheap, readily available, non-toxic and renewable C1 resource, and its efficient chemical utilization has become the focus of current industry and academia. 2 Intrinsic thermodynamic stability and kinetic inertness enable CO 2 High efficiency and high selectivity conversion remains a daunting challenge. 2 As raw materials, through the development of advanced catalytic technology, it can be converted into various high value-added chemical and energy products, such as methanol, urea, formic acid, oxazolidinone, quinazolinone, etc. 2 The synthesis of cyclic carbonates by cycloaddition reaction with epoxides has attracted widespread attention. On the one hand, the reaction has 100% atom economy and can replace the traditional phosgene process to meet the requirements of green chemistry and environmental protection; on the other hand, cyclic carbonates are a very important class of chemical products with excellent physical and chemical properties, such as high boiling point, high polarity, low volatility, good biodegradability and solubility, and are widely used in the fields of chemical industry, medicine, polymers, etc.
[0003] For chemical fixation of CO 2In the synthesis of cyclic carbonates, the homogeneous potassium iodide catalytic system is currently widely used in the industry, but the production scale is relatively small, and the catalytic process requires harsh reaction conditions (180-200°C, 5-8MPa). To this end, relevant literature has reported a series of homogeneous catalytic systems, including ionic liquids, alkali metal salts, metal complexes, low eutectic solvents, etc., but the separation process of homogeneous catalysts and products is complicated, requiring a large amount of volatile organic solvents, and high energy consumption, which limits its large-scale application. In order to solve the problem of catalyst separation, people have developed and reported a series of different types of heterogeneous catalysts, such as immobilized ionic liquids, nitrogen-doped carbon, hybrid organosilicon, metal organic frameworks, and covalent organic frameworks. Although the development of heterogeneous catalysts has solved the problem of separation from products to a certain extent, there are still problems such as poor catalyst structural stability and low catalytic activity, which require high temperature and high pressure for the reaction. Metal organic frameworks (MOFs, also known as porous coordination polymers-PCPs) are a class of porous materials with topological structures. They are synthesized by self-assembly of metal-containing nodes (secondary building blocks) and organic ligands. Therefore, MOF, as an inorganic-organic hybrid nanoporous material, consists of two parts and has significant diversity compared with traditional solid materials. It has the characteristics of high specific surface area, ultra-high porosity, rich active centers, and adjustable structure. Therefore, MOF has great potential in adsorption, gas separation and storage, heterogeneous catalysis, photocatalysis, hydrogen evolution, oxygen evolution, CO 2 It has broad application prospects in many aspects such as reduction, drug delivery, etc. At present, MOFs have been widely used in the design and development of new structures and heterogeneous catalysis of CO 2 There are more and more reports on the conversion and synthesis of cyclic carbonates. Among them, for MOFs catalysts that are easy to obtain, their catalytic activity or structural stability is often insufficient; while for MOFs-based catalysts with excellent catalytic activity, their preparation process is relatively complicated and requires the use of expensive ligands. Therefore, it is necessary to design and develop new MOFs-based catalysts that are simple to prepare, cheap and easy to obtain, and have both excellent catalytic activity and structural stability, so as to achieve CO conversion under mild or even normal temperature and pressure conditions. 2 Highly selective transformation is still an urgent need. Summary of the invention
[0004] The purpose of the present invention is to provide a ZIF-8@In 2 O 3 The present invention discloses a method for synthesizing cyclic carbonate by converting carbon dioxide into cyclic carbonate by catalysis of composite materials. The catalyst of the present invention is simple to prepare, the raw materials are cheap and readily available, the stability is high, and the catalyst can be recycled. The catalyst can catalyze CO 2 with high selectivity and cleanness under mild (or normal temperature and pressure) and solvent-free conditions. 2 Synthesize cyclic carbonates with epoxides to CO 2 Realize high-value resource utilization.
[0005] In order to achieve the above object, the present invention adopts the following technical solution:
[0006] The present invention provides a ZIF-8@In 2 O 3 A method for synthesizing cyclic carbonates by converting carbon dioxide into cyclic carbonates catalyzed by composite materials, wherein carbon dioxide and epoxy compounds are used as raw materials, ZIF-8@In 2 O 3 The composite material is used as a catalyst, and tetrabutylammonium bromide is used as a co-catalyst to synthesize cyclic carbonate by cycloaddition of epoxy compounds and atmospheric carbon dioxide. 2 O 3 The composite material is composed of ZIF-8 and hollow prismatic In 2 O 3 Prepared by in-situ composite.
[0007] Preferably, the ZIF-8@In 2 O 3 A method for preparing a composite material, comprising:
[0008] Step 1: Preparation of In with hollow prism structure 2 O 3 ;
[0009] Step 2: In the hollow prism structure 2 O 3 Disperse evenly in the solvent, add zinc nitrate hexahydrate and stir until completely dissolved to obtain solution A; dissolve 2-methylimidazole in the solvent to obtain solution B; slowly add solution B to solution A and stir, filter to obtain ZIF-8@In 2 O 3 Nanocomposite materials.
[0010] Preferably, the hollow prism structure In 2 O 3 A preparation method comprising:
[0011] Step (1): adding hydrated indium nitrate and terephthalic acid to a solvent respectively and mixing them, stirring the obtained mixture until it becomes clear and transparent, placing it in an oil bath for heating and reacting, and after the mixture cools to room temperature, washing it by centrifugation, and drying it to obtain a MIL-68 (In) precursor;
[0012] Step (2): Place the MIL-68 (In) precursor obtained in step (1) into a tube furnace and preheat in air at a heating rate of 5 °C min -1 , then in N 2 In the atmosphere, the solid is heated to 400-500°C at the same heating rate and kept for 2-3 hours. After the calcination, it is cooled and ground to obtain In 2O 3 powder.
[0013] Preferably, the reaction temperature of step (1) is 90-120° C., and the reaction time is 2-4 hours.
[0014] Preferably, the mass ratio of hydrated indium nitrate to terephthalic acid in step (1) is 1:1.
[0015] Preferably, the preheating temperature of step (2) is 110-140° C., and the preheating time is 2-3 hours.
[0016] Preferably, the In 2 O 3 The mass ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:1-2.5, and the mass ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:2.2.
[0017] Preferably, the epoxy compound has the following structural formula:
[0018]
[0019] Preferably, the amount of the catalyst is 5% to 10% of the mass of the epoxy compound, and the amount of the co-catalyst is 5% to 10% of the molar amount of the epoxy compound.
[0020] Preferably, the cycloaddition reaction pressure is 0.1 MPa, the reaction temperature is 30 to 80° C., and the cycloaddition reaction time is 6 to 24 hours.
[0021] Beneficial Effects of the Invention
[0022] The present invention provides a ZIF-8@In 2 O 3 A method for synthesizing cyclic carbonates by converting carbon dioxide into cyclic carbonates catalyzed by composite materials, wherein carbon dioxide and epoxy compounds are used as raw materials, ZIF-8@In 2 O 3 The composite material is used as a catalyst, and tetrabutylammonium bromide is used as a co-catalyst to synthesize cyclic carbonate by cycloaddition of epoxy compounds and atmospheric carbon dioxide. 2 O 3 The composite material is composed of ZIF-8 and hollow prismatic In 2 O 3 The ZIF-8@In 2 O 3The nanocomposite catalyst is easy to prepare, the raw materials are cheap and readily available, and it has the dual functionality of adsorbing and activating carbon dioxide and epoxides, and can achieve highly selective synthesis of cyclic carbonates under mild conditions, and is environmentally friendly; the catalyst can catalyze the cycloaddition reaction of epoxides with different substituents and carbon dioxide, and after the reaction, the catalyst and the product can be separated by simple filtration or centrifugation, and has excellent universality and recycling performance. Compared with the prior art, the catalyst of the present invention has been significantly improved in catalyst preparation, catalyst cost, catalytic activity and stability, and can achieve clean catalytic conversion of CO under mild conditions. 2 The synthesis of cyclic carbonates has broad potential for large-scale development. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The ZIF-8@In prepared by the present invention 2 O 3 -1.5 composites with ZIF-8 and In 2 O 3 Infrared comparison image of
[0024] Figure 2 The ZIF-8@In prepared by the present invention 2 O 3 -1.5 and ZIF-8@In 2 O 3 -2.5 Composites with ZIF-8 and In 2 O 3 Powder X-ray diffraction comparison chart of;
[0025] Figure 3 The ZIF-8 and In prepared by the present invention 2 O 3 and ZIF-8@In 2 O 3 -1.5 scanning electron microscopy and transmission electron microscopy images. DETAILED DESCRIPTION
[0026] The present invention provides a ZIF-8@In 2 O 3 A method for synthesizing cyclic carbonates by converting carbon dioxide into cyclic carbonates catalyzed by composite materials, wherein carbon dioxide and epoxy compounds are used as raw materials, ZIF-8@In 2 O 3 The composite material is used as a catalyst, and tetrabutylammonium bromide is used as a co-catalyst to synthesize cyclic carbonate by cycloaddition of epoxy compounds and atmospheric carbon dioxide. 2 O 3 The composite material is composed of ZIF-8 and hollow prismatic In 2 O3 In-situ composite preparation. 2 The reaction equation for preparing cyclic carbonate by cycloaddition with epoxy compounds is as follows:
[0027]
[0028] Wherein R is an alkyl group, a halogenated alkyl group, or an aromatic group.
[0029] According to the present invention, the ZIF-8@In 2 O 3 A method for preparing a composite material, comprising:
[0030] Step 1: Preparation of In with hollow prism structure 2 O 3 ; Specifically:
[0031] Step (1): adding hydrated indium nitrate and terephthalic acid to a solvent respectively and mixing them, the solvent is preferably N,N-dimethylformamide, stirring the obtained mixture until it is clear and transparent, and then placing it in an oil bath for heating reaction, the temperature of the heating reaction is preferably 90-120° C., and the reaction time is preferably 2-4 hours. After the mixture cools to room temperature, it is centrifuged, preferably washed three times with N,N-dimethylformamide and anhydrous ethanol respectively, and vacuum dried at 60-80° C. for 6-12 hours to obtain a MIL-68 (In) precursor; the mass ratio of hydrated indium nitrate to terephthalic acid is preferably 1:1;
[0032] Step (2): Place the MIL-68 (In) precursor obtained in step (1) into a tube furnace and preheat it in air. The preheating temperature is preferably 110-140°C, the preheating time is preferably 2-3h, and the heating rate is 5°C min -1 , then in N 2 In the atmosphere, the solid is heated to 400-500°C at the same heating rate and kept for 2-3 hours. After the calcination, it is cooled and ground to obtain In 2 O 3 powder.
[0033] Step 2: In the hollow prism structure 2 O 3 The mixture is uniformly dispersed in a solvent, preferably methanol, and then zinc nitrate hexahydrate is added and stirred until completely dissolved, and the stirring time is preferably 0.5-1.0 hours to obtain solution A; 2-methylimidazole is dissolved in a solvent, and the solvent is preferably methanol to obtain solution B; solution B is slowly added to solution A and stirred, and the stirring temperature is preferably room temperature, and the stirring time is preferably 12-24 hours, and filtered to obtain ZIF-8@In 2 O 3The nanocomposite material was washed three times with anhydrous methanol and anhydrous ethanol respectively, and dried under vacuum at 60-80°C for 6-12 hours. The obtained product was recorded as ZIF-8@In 2 O 3 -x, where x represents zinc nitrate hexahydrate and In 2 O 3 The mass ratio of In 2 O 3 The mass ratio of zinc nitrate hexahydrate to 2-methylimidazole is preferably 1:1-2.5, more preferably 1:1.5. The mass ratio of zinc nitrate hexahydrate to 2-methylimidazole is preferably 1:2.2.
[0034] According to the present invention, the epoxy compound has the following structural formula:
[0035]
[0036] Wherein, R is an alkyl group, a halogenated alkyl group or an aromatic group. Preferably, it is the following structure:
[0037]
[0038] According to the present invention, the amount of the catalyst is preferably 5% to 10% of the mass of the epoxy compound, more preferably 8%, and the amount of the co-catalyst is preferably 5% to 10% of the molar amount of the epoxy compound.
[0039] According to the present invention, the cycloaddition reaction pressure is preferably 0.1 MPa, the reaction temperature is preferably 30 to 80° C., and the cycloaddition reaction time is preferably 6 to 24 hours.
[0040] The present invention will be further described in detail in conjunction with specific implementation methods. The following examples are only used to illustrate the present invention and are not intended to limit the present invention.
[0041] Example 1 Hollow Prism Structure In 2 O 3 Preparation
[0042] 0.30 g of hydrated indium nitrate and 0.30 g of terephthalic acid were mixed with 100 mL of N, N-dimethylformamide solvent. The mixture was stirred at room temperature until clear and transparent, then placed in an oil bath and heated to 110°C. The mixture was reacted for 3 hours under condensing conditions. After the mixture cooled to room temperature, it was centrifuged to obtain a white solid, which was washed three times with N, N-dimethylformamide and anhydrous ethanol, respectively, and dried at 70°C in vacuum for 8 hours to obtain a MIL-68 (In) precursor. The obtained MIL-68 (In) precursor was placed in a tube furnace and preheated at 120°C in air for 2 hours, with a heating rate of 5°C min -1 , then in N 2The solid was heated to 500°C at the same heating rate and kept for 2 hours under the atmosphere. After calcination, In 2 O 3 powder.
[0043] Example 2 ZIF-8@In 2 O 3 Preparation of nanocomposites
[0044] Weigh 0.20 g In 2 O 3 Evenly dispersed in 40mL methanol solution, and then weighed 0.30g zinc nitrate hexahydrate (In 2 O 3 The mass ratio of zinc nitrate hexahydrate is 1:1.5), and then added to In 2 O 3 The dispersion was stirred for 0.5 hours to allow Zn 2+ Fully attached to In 2 O 3 Then weigh 0.66 g of 2-methylimidazole and dissolve it in 40 mL of methanol solution (the mass ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:2.2). After it is fully dissolved, add it to the above solution, stir at room temperature for 24 hours, and then filter to obtain ZIF-8@In 2 O 3 The nanocomposite material was washed three times with anhydrous methanol and anhydrous ethanol respectively, and dried under vacuum at 60°C for 12 hours. The obtained product was named ZIF-8@In 2 O 3 -1.5.
[0045] In this way, by changing In 2 O 3 The mass ratio of zinc nitrate hexahydrate was 1:1, 1:2 and 1:2.5, respectively, to prepare ZIF-8@In 2 O 3 -1, ZIF-8@In 2 O 3 -2 and ZIF-8@In 2 O 3 -2.5.
[0046] Figure 1 The ZIF-8@In obtained in Example 2 of the present invention 2 O 3 -1.5 composite material with ZIF-8 (Comparative Example 1) and In 2 O 3 Infrared comparison of ZIF-8@In 2 O 3-1.5 composites integrating ZIF-8 and In 2 O 3 The characteristic absorption peaks of the composite material were successfully prepared.
[0047] Figure 2 The ZIF-8@In obtained in Example 2 of the present invention 2 O 3 -1.5 and ZIF-8@In 2 O 3 -2.5 composite material with ZIF-8 (Comparative Example 1) and In 2 O 3 Powder X-ray diffraction comparison diagram; It can be seen from the figure that the prepared composite material integrates ZIF-8 and In 2 O 3 The characteristic diffraction peaks are present, and after compounding, it still maintains excellent crystallinity.
[0048] Figure 3 ZIF-8 (Comparative Example 1), In 2 O 3 and ZIF-8@In obtained in Example 2 of the present invention 2 O 3 -1.5 scanning electron microscope and transmission electron microscope images. Among them, (a) and (b) are scanning electron microscope images of ZIF-8; (c), (d) and (i) are ZIF-8@In 2 O 3 -1.5 scanning electron micrographs; (e) and (f) are In 2 O 3 Transmission electron microscopy images of ZIF-8@In 2 O 3 -1.5 transmission electron microscope image. It can be seen from the figure that ZIF-8 has a rhombic dodecahedral structure, uniform shape, and smooth surface; In prepared by high-temperature calcination of MIL-68 (In) precursor 2 O 3 It shows a regular prismatic structure; ZIF-8 and In 2 O 3 After in-situ compounding, ZIF-8 is evenly dispersed in In 2 O 3 The surface forms fine nanoparticles, increasing the In 2 O 3 Surface roughness; In addition, ZIF-8@In 2 O 3 -1.5 retains the hollow core-shell columnar structure, further confirming that ZIF-8@In 2 O 3-x nanocomposite materials were successfully prepared.
[0049] Example 3
[0050] Take the reactant epichlorohydrin and the catalyst ZIF-8@In prepared in Example 2 2 O 3 -1.5 and TBAB co-catalysts were added sequentially to connect CO 2 A 25 mL reaction tube with a balloon (0.1 MPa pressure) containing 5.0 mmol (0.46 g) of epichlorohydrin, ZIF-8@In 2 O 3 -1.5 0.037 g, accounting for 8 wt% (1.8 mol%, calculated based on metal zinc) of the reactants, TBAB 0.05 mmol, accounting for 10 mol% of the reactants; CO was slowly introduced into the reaction tube. 2 To remove the remaining air inside; then seal the reaction tube and connect the CO 2 balloon; the reaction mixture was heated to 40°C and the reaction was continued for 20 hours; after the reaction was completed, the reaction tube was cooled to room temperature in an ice water bath, and the product was analyzed by gas chromatography-mass spectrometry. The yield of chloropropylene carbonate was 95%, and the selectivity was ≥99%.
[0051] Example 4
[0052] Take the reactant epichlorohydrin and the catalyst ZIF-8@In prepared in Example 2 2 O 3 -2 and TBAB co-catalysts were added sequentially to connect CO 2 A 25 mL reaction tube with a balloon (0.1 MPa pressure) containing 5.0 mmol (0.46 g) of epichlorohydrin, ZIF-8@In 2 O 3 -2 0.037g, accounting for 8wt% of the reactant mass, TBAB 0.05mmol, accounting for 10mol% of the reactant molar mass; CO was slowly introduced into the reaction tube. 2 To remove the remaining air inside; then seal the reaction tube and connect the CO 2 balloon; the reaction mixture was heated to 40°C and the reaction was continued for 20 hours; after the reaction was completed, the reaction tube was cooled to room temperature in an ice water bath, and the product was analyzed by gas chromatography-mass spectrometry. The yield of chloropropylene carbonate was 92% and the selectivity was ≥99%.
[0053] Example 5
[0054] Take the reactant epichlorohydrin and the catalyst ZIF-8@In prepared in Example 2 2 O 3 -1.5 and TBAB co-catalysts were added sequentially to connect CO2 A 25 mL reaction tube with a balloon (0.1 MPa pressure) containing 5.0 mmol (0.46 g) of epichlorohydrin, ZIF-8@In 2 O 3 -1.5 0.046 g, accounting for 10 wt% (1.0 mol%, calculated based on metal indium) of the reactants, 0.05 mmol of TBAB, accounting for 10 mol% of the molar amount of the reactants; CO was slowly introduced into the reaction tube. 2 To remove the remaining air inside; then seal the reaction tube and connect the CO 2 balloon; the reaction mixture was heated to 30°C and the reaction was continued for 24 hours; after the reaction was completed, the reaction tube was cooled to room temperature in an ice water bath, and the product was analyzed by gas chromatography-mass spectrometry. The yield of chloropropylene carbonate was 94%, and the selectivity was ≥99%.
[0055] Example 6
[0056] Take the reactant epichlorohydrin and the catalyst ZIF-8@In prepared in Example 2 2 O 3 -1.5 and TBAB co-catalysts were added sequentially to connect CO 2 A 25 mL reaction tube with a balloon (0.1 MPa pressure) containing 5.0 mmol (0.46 g) of epichlorohydrin, ZIF-8@In 2 O 3 -1.5 0.046 g, accounting for 10 wt% of the reactant mass, TBAB 0.05 mmol, accounting for 10 mol% of the reactant molar mass; CO was slowly introduced into the reaction tube. 2 To remove the remaining air inside; then seal the reaction tube and connect the CO 2 balloon; the reaction mixture was heated to 80°C and the reaction was continued for 6 hours; after the reaction was completed, the reaction tube was cooled to room temperature in an ice water bath, and the product was analyzed by gas chromatography-mass spectrometry. The yield of chloropropylene carbonate was 89% and the selectivity was ≥99%.
[0057] Example 7
[0058] The experimental process is the same as in Example 3, using ZIF-8@In prepared in Example 2 2 O 3 -1.5 is the catalyst, TBAB is the co-catalyst, and different epoxides are selected to react with carbon dioxide at 40°C, 0.1 MPa, 5.0 mmol of epoxide, 8 wt% of catalyst and 10 mol% of co-catalyst for 20 hours. The results are shown in Table 1.
[0059] Table 1 ZIF-8@In 2 O 3-1.5 / TBAB catalyzed cycloaddition reaction of carbon dioxide with different epoxides
[0060]
[0061] Embodiment 8-13
[0062] The specific experimental conditions and steps were the same as those in Example 3, except that the catalyst ZIF-8@In 2 O 3 -1.5 was changed to ZIF-8@In separated and recovered in Example 3 2 O 3 -1.5, and 6 recycling experiments were carried out under the same conditions. The results are shown in Table 2.
[0063] Table 2 Experimental results of catalyst recycling in Examples 8-13
[0064]
[0065] Comparative Example 1: Preparation of ZIF-8
[0066] 0.30 g of zinc nitrate hexahydrate was weighed and dissolved in 40 mL of methanol to obtain solution A, and 0.66 g of 2-methylimidazole was similarly dissolved in 40 mL of methanol to obtain solution B. Solution B was then slowly added dropwise to solution A, and the resulting mixed solution was stirred at room temperature for 24 hours and filtered to collect a white solid. The solid was washed three times with anhydrous methanol and anhydrous ethanol, respectively, and vacuum dried at 60°C for 12 hours to obtain ZIF-8 powder.
[0067] Comparative Example 2: Using ZIF-8 as a catalyst to catalyze CO 2 Applications of Cycloaddition Reactions
[0068] The activity of different catalysts was compared under the same catalytic reaction conditions as in Example 3, as follows: epichlorohydrin, the ZIF-8 catalyst prepared in Comparative Example 1, and the TBAB co-catalyst were added to the CO 2 A 25 mL reaction tube was filled with a balloon (0.1 MPa pressure), wherein epichlorohydrin 5.0 mmol (0.46 g), ZIF-8 accounted for 1.8 mol% of the molar amount of the reactants (calculated based on metallic zinc), and TBAB 0.05 mmol, accounted for 10 mol% of the molar amount of the reactants; CO was slowly introduced into the reaction tube. 2 To remove the remaining air inside; then seal the reaction tube and connect the CO 2 balloon; the reaction mixture was heated to 40°C and the reaction was continued for 20 hours; after the reaction was completed, the reaction tube was cooled to room temperature in an ice water bath, and the product was analyzed by gas chromatography-mass spectrometry. The yield of chloropropylene carbonate was 56%, and the selectivity was ≥99%.
[0069] Comparative Example 3: In 2 O 3 As a catalyst for CO 2 Applications of Cycloaddition Reactions
[0070] The activity of different catalysts was compared under the same catalytic reaction conditions as in Example 5, as follows: 2 O 3 and TBAB co-catalyst were added to connect CO 2 A 25 mL reaction tube was filled with a balloon (0.1 MPa pressure), wherein epichlorohydrin 5.0 mmol (0.46 g), In 2 O 3 1.0 mol% of the reactant molar amount (calculated according to metal indium), 0.05 mmol of TBAB, accounting for 10 mol% of the reactant molar amount; CO was slowly introduced into the reaction tube. 2 To remove the remaining air inside; then seal the reaction tube and connect the CO 2 balloon; the reaction mixture was heated to 30°C and the reaction was continued for 24 hours; after the reaction was completed, the reaction tube was cooled to room temperature in an ice water bath, and the product was analyzed by gas chromatography-mass spectrometry. The yield of chloropropylene carbonate was 43% and the selectivity was ≥99%.
[0071] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art may still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for synthesizing cyclic carbonates by catalyzing carbon dioxide conversion using a ZIF-8@In2O3 composite material, characterized in that: The method uses carbon dioxide and epoxy compounds as raw materials, a ZIF-8@In2O3 composite material as a catalyst, and tetrabutylammonium bromide as a co-catalyst to synthesize cyclic carbonates by cycloaddition of epoxy compounds and atmospheric carbon dioxide. The ZIF-8@In2O3 composite material is prepared by in-situ composite preparation of ZIF-8 and In2O3 with a hollow prism structure.
2. The method for synthesizing cyclic carbonate by catalyzing carbon dioxide conversion using a ZIF-8@In2O3 composite material according to claim 1, characterized in that: The preparation method of the ZIF-8@In2O3 composite material comprises: Step 1: Preparation of In2O3 with hollow prism structure; Step 2: Evenly disperse the hollow prism structured In2O3 in a solvent, add zinc nitrate hexahydrate and stir until completely dissolved to obtain solution A; dissolve 2-methylimidazole in a solvent to obtain solution B; slowly add solution B into solution A and stir, and filter to obtain a ZIF-8@In2O3 nanocomposite material.
3. The method for synthesizing cyclic carbonate by catalyzing carbon dioxide conversion using a ZIF-8@In2O3 composite material according to claim 2, characterized in that: The method for preparing the hollow prism structure In2O3 comprises: Step (1): adding hydrated indium nitrate and terephthalic acid to a solvent respectively and mixing them, stirring the obtained mixture until it becomes clear and transparent, placing it in an oil bath for heating and reacting, and after the mixture cools to room temperature, washing it by centrifugation, and drying it to obtain a MIL-68 (In) precursor; Step (2): Place the MIL-68 (In) precursor obtained in step (1) into a tube furnace and preheat in air at a heating rate of 5 °C min -1 Then, in a N2 atmosphere, the solid is heated to 400-500°C at the same heating rate and retained for 2-3 hours. After calcination, In2O3 powder is obtained by cooling and grinding.
4. The method for synthesizing cyclic carbonate by catalyzing carbon dioxide conversion using a ZIF-8@In2O3 composite material according to claim 3, characterized in that: The reaction temperature of step (1) is 90-120° C., and the reaction time is 2-4 hours.
5. The method for synthesizing cyclic carbonate by catalyzing carbon dioxide conversion using a ZIF-8@In2O3 composite material according to claim 3, characterized in that: The mass ratio of the hydrated indium nitrate to terephthalic acid in step (1) is 1:
1.
6. The method for synthesizing cyclic carbonate by catalyzing carbon dioxide conversion using a ZIF-8@In2O3 composite material according to claim 3, characterized in that: The preheating temperature of step (2) is 110-140° C., and the preheating time is 2-3 hours.
7. The method for synthesizing cyclic carbonate by catalyzing carbon dioxide conversion using a ZIF-8@In2O3 composite material according to claim 1, characterized in that: The mass ratio of In2O3 to zinc nitrate hexahydrate is 1:1-2.5, and the mass ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:2.
2.
8. The method for synthesizing cyclic carbonate by catalyzing carbon dioxide conversion using a ZIF-8@In2O3 composite material according to claim 1, characterized in that: The epoxy compound structural formula is as follows:
9. The method for synthesizing cyclic carbonate by catalyzing carbon dioxide conversion using a ZIF-8@In2O3 composite material according to claim 1, characterized in that: The amount of the catalyst is 5% to 10% of the mass of the epoxy compound, and the amount of the co-catalyst is 5% to 10% of the molar amount of the epoxy compound.
10. The method for synthesizing cyclic carbonate by catalyzing carbon dioxide conversion using a ZIF-8@In2O3 composite material according to claim 1, characterized in that: The cycloaddition reaction pressure is 0.1 MPa, the reaction temperature is 30-80° C., and the cycloaddition reaction time is 6-24 hours.
Citation Information
Cited By
Cyclic carbonate for electrolyte, preparation method of cyclic carbonate and electrolyte
CN120289415A
Method for synthesizing cyclic carbonate by catalyzing conversion of carbon dioxide through MIL-68 (In / Bi)-NH2 loaded carbon nitride
CN121198356A
Polymerization ionic liquid catalyst as well as preparation method and application thereof
CN122277807A